Analysis of Consumer Intentions to Avoid Purchasing Electric Motorcycle Products: An Innovation Resistance Theory Approach and the Moderating Role of Green Trust - Damayanti, Nenty; Nurmahdi, Adi (International Journal Labs, 2026)
Electric motorcycles are promoted as an environmentally friendly transportation solution to reduce carbon emissions and support sustainable development. However, consumer resistance to purchasing electric motorcycles remains a major barrier, particularly in developing countries such as Indonesia. This study aims to analyze the effects of innovation barriers on Intention to Resist Electric Motorcycle Product Purchase, namely Usage Barrier, Value Barrier, Risk Barrier, Tradition Barrier, and Image Barrier, and to examine the moderating role of Green Trust. The study employs a quantitative approach using PLS-SEM. Data were collected from 221 respondents aged 18–56 who live or work in Jabodetabek and Yogyakarta. The findings indicate that Usage Barrier, Value Barrier, Tradition Barrier, and Image Barrier have a positive and significant effect on consumers’ intention to resist purchasing electric motorcycles, while Risk Barrier is not significant. Among all barriers, the Tradition Barrier is the most dominant factor. In addition, Green Trust is not proven to significantly moderate the relationships between the innovation barriers and the intention to resist purchase. This study extends the application of Innovation Resistance Theory (IRT) in the context of green products and offers practical recommendations for industry stakeholders to strengthen credibility and foster more positive perceptions of electric motorcycles.